2018
DOI: 10.1002/pbc.27525
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality as complementary pain therapy in hospitalized patients with sickle cell disease

Abstract: Objective Due to incomplete management of vaso‐occlusive pain episodes (VOE) in patients with sickle cell disease (SCD), we sought to determine if immersive VR would be feasible for inpatients. Secondarily, we hypothesized that a single VR session would improve the VOE pain experience. Procedures Consecutive patients with SCD eight years and older admitted for VOE were offered one 15‐minute VR session, utilizing a relaxing underwater world specifically created for pediatric patients and to minimize potential s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 51 publications
6
65
0
1
Order By: Relevance
“…Moreover, subjective clinician, parent, and patient report of engagement, distraction, immersion, and enjoyment of the process were consistent with prior work [14,23,24]. The multisession daily reports indicated decreased pain, fear, avoidance, and functional impairments across VR sessions and this result is consistent with prior work [15,[25][26][27]. Given that these changes were observed in the context of IIPT, it is possible the changes reflect general versus VR-specific effects, and thus it is necessary to conduct a more controlled pilot trial to measure the impact of VR on pain rehabilitation.…”
Section: Principal Findingssupporting
confidence: 81%
“…Moreover, subjective clinician, parent, and patient report of engagement, distraction, immersion, and enjoyment of the process were consistent with prior work [14,23,24]. The multisession daily reports indicated decreased pain, fear, avoidance, and functional impairments across VR sessions and this result is consistent with prior work [15,[25][26][27]. Given that these changes were observed in the context of IIPT, it is possible the changes reflect general versus VR-specific effects, and thus it is necessary to conduct a more controlled pilot trial to measure the impact of VR on pain rehabilitation.…”
Section: Principal Findingssupporting
confidence: 81%
“…Results showed the feasibility of the study and a reduction of median pain intensity: Pre-VR = 7.3; Post-VR = 3.0. In addition, the number of affected body areas decreased: pre-VR = 3.0 post-VR = 2.0 [5]. Al-Halabi et al used VR to reduce pain in child behavior management during an inferior alveolar nerve block.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed the pain reduction by comparing the indicated values with and without VR, with conflicting results. These studies reported a pain reduction of: 4/10 [5], 2.57/5 [10], 1.78 and 1.39 [8], 2.89 ± 0.2/10 [7], 3/10 [6], 1.15 ± 0.28/5 [12], 2.37/10 [13], and other didn’t show statistical differences [9, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Acute pain crises from SCD are often incompletely managed, and patients are often treated with opioids with minimal success 9 . Immersive VR has been shown to decrease pain intensity and pain descriptors for pediatric patients in acute pain crisis from SCD 10 . To date, there are no reports of the use of VR for placement of an epidural catheter in an adolescent patient but our experience is consistent with studies that endorse its use to reduce pain and anxiety in children during invasive procedures 6 .…”
Section: Discussionmentioning
confidence: 99%